A területfejlesztés megújítási iránya, az ipari körzetek - Dusek, Tamás (Tér és Társadalom, 1999)
The examination of industrial districts, as one of the local economy development model is based on Alfred Marshall’s activity. The study performs the original theoretic of Marshall and the modernisation of it. It deals with the economic and organisation changes existed in the background of the theory and the development of flexible production systems displacing the post-fordist model. It presents some selected examples of the successful economy development models. The most detailed example is the Third Italian model. The main lesson of the study that a suc- cessful economic development couldn’t be achieved without active contribution of local actors of economy and society. Regional policy can contribute to this process primarily with the promotion of establishment and initiation of public goods, and relationship between digerent actors, and with the building-up of institutional infrastructure.